2017
DOI: 10.4269/ajtmh.16-0431
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Leishmania guyanensis and Human Immunodeficiency Virus–Acquired Immune Deficiency Syndrome: Report of a Case of Disseminated Cutaneous Leishmaniasis in Ecuador

Abstract: Abstract. Reported herein is the first case of Leishmania-human immunodeficiency virus (HIV) coinfection in Ecuador. In Ecuador, HIV infections overlap endemic areas of leishmaniasis. Immunosuppression is a wellestablished risk factor for developing severe disease. This is a severe case of a 32-year-old man presenting with disseminated pleomorphic ulcers, papules, and cutaneous plaque-like lesions over his whole body. Numerous amastigotes were observed in both skin scrapings and biopsies. The sequence of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The worsening of clinical manifestations, multiple lesions and high degree of relapses post-treatment in ATL patients co-infected with HIV were previously described ( Rosatelli et al, 1998 ; Puig and Pradinaud, 2003 ; Lindoso et al, 2009 , 2016 ; Giavedoni et al, 2015 ; Calvopina et al, 2017 ). In a study of fifteen cases of AIDS/TL, Lindoso et al (2009) observed mucosal lesions progress in 80% of the patients, disseminated lesions in 60% and genital lesions in 27% of the patients.…”
Section: The Host Point Of Viewmentioning
confidence: 75%
“…The worsening of clinical manifestations, multiple lesions and high degree of relapses post-treatment in ATL patients co-infected with HIV were previously described ( Rosatelli et al, 1998 ; Puig and Pradinaud, 2003 ; Lindoso et al, 2009 , 2016 ; Giavedoni et al, 2015 ; Calvopina et al, 2017 ). In a study of fifteen cases of AIDS/TL, Lindoso et al (2009) observed mucosal lesions progress in 80% of the patients, disseminated lesions in 60% and genital lesions in 27% of the patients.…”
Section: The Host Point Of Viewmentioning
confidence: 75%
“…Interestingly, in contrast to DCL and CL with multiple lesions in immunosuppressed patients - which are associated with high in situ parasite load - Leishmania amastigotes are not easily found in DL lesions and the Th1 response against Leishmania antigens is preserved in DL. 3,16-19…”
Section: Immunological Factorsmentioning
confidence: 99%
“…Moreover, Montenegro test is generally negative and the lesions exhibit a large number of amastigotes in the infiltrate. 18,19…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leishmania sp. occurs in a wide range of hosts [ 83 , 84 , 85 , 86 , 87 , 88 ], including human [ 89 ] and non-human primates [ 48 ]. In NHPs, experimental [ 90 ] and natural infections [ 91 ] have been registered.…”
Section: Introductionmentioning
confidence: 99%